2007
DOI: 10.1158/1541-7786.mcr-06-0384
|View full text |Cite
|
Sign up to set email alerts
|

A Complex of EpCAM, Claudin-7, CD44 Variant Isoforms, and Tetraspanins Promotes Colorectal Cancer Progression

Abstract: High expression of EpCAM and the tetraspanin CO-029 has been associated with colorectal cancer progression. However, opposing results have been reported on CD44 variant isoform v6 (CD44v6) expression. We recently noted in rat gastrointestinal tumors that EpCAM, claudin-7, CO-029, and CD44v6 were frequently coexpressed and could form a complex. This finding suggested the possibly that the complex, rather than the individual molecules, could support tumor progression. The expression of EpCAM, claudin-7, CO-029, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
222
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(238 citation statements)
references
References 73 publications
(105 reference statements)
13
222
2
1
Order By: Relevance
“…For example, claudin-11 interacts with OAP-1 to form a complex with integrins, which results in increased oligodendrocyte proliferation and migration (Tiwari-Woodruff et al, 2001). In addition, claudin-7 has been shown to form a complex with tetraspanins, EpCam and CD44 in colorectal cancers, and expression of these molecules was inversely correlated with disease-free survival (Kuhn et al, 2007). Interestingly, we performed immunofluorescence staining for claudin-2 in MDA-MB-231 cells and found that claudin-2 displays a punctate staining pattern when cells are plated on fibronectin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, claudin-11 interacts with OAP-1 to form a complex with integrins, which results in increased oligodendrocyte proliferation and migration (Tiwari-Woodruff et al, 2001). In addition, claudin-7 has been shown to form a complex with tetraspanins, EpCam and CD44 in colorectal cancers, and expression of these molecules was inversely correlated with disease-free survival (Kuhn et al, 2007). Interestingly, we performed immunofluorescence staining for claudin-2 in MDA-MB-231 cells and found that claudin-2 displays a punctate staining pattern when cells are plated on fibronectin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Tetraspanin 8 affects protein trafficking and is known to influence a wide variety of physiological processes. 19 GWA studies for schizophrenia and bipolar disorder revealed association between TSPAN8 and both psychiatric disorders. 20 Finally,…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the tumor type, high EpC expression correlates with tumor grading and/or tumor-nodemetastasis staging and/or decreased overall and poor diseasefree survival (4,5,13,14). EpC has also been described as a cancer-initiating cell marker of mammary, colorectal, and pancreatic cancers (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the metastatic BSp73ASML subline, EpC is associated with claudin-7 (cld-7), CD44v, several integrins, and the tetraspanin D6.1A (33)(34)(35), where only the EpC-cld-7 association is based on a direct protein-protein interaction (14,34). Tetraspanins are located in glycolipid-enriched membrane microdomains (14,34), called tetraspanin-enriched membrane microdomains (TEM), which serve as a signaling platform (36,37). According to its association with tetraspanins, the EpC-cld-7 complex is supposed to be TEM located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation